Effects of carbohydrate ingestion on acute leukocyte, cortisol, and interleukin-6 response in high-intensity long-distance running - Ihalainen, J. K.; Vuorimaa, T.; Puurtinen, R.; Hämäläinen, I.; Mero, A. A. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate the effect of ingestion of fluids with different carbohydrate concentrations (0, 1.5, and 7%) on the acute immune stress responses after high-intensity long-distance running. Continuous 18- to 20-km run was performed at 75% of maximal oxygen uptake with carbohydrate supplementation (CHO7%, 7% carbohydrate solution) and low-carbohydrate supplementation (lowCHO1.5%, 1.5% carbohydrate solution) in a randomized, double-blind, placebo (PLA) controlled design. Seven recreational runners (4 men and 3 women) completed all 3 trials. Blood was collected at baseline (PRE) and immediately after the run (POST). The running task induced significant (p < 0.05) increases in leukocyte (white blood cells), neutrophil, and interleukin-6 (IL-6) counts in every trial. There was a significant (p < 0.05) increase in cortisol with PLA and lowCHO1.5% but not with CHO7%. Increase in total leukocyte and neutrophil concentration was significantly lower with CHO7% compared with PLA (p < 0.05). Postexercise IL-6 levels were significantly elevated when compared with baseline in all conditions (p < 0.05). Interleukin-6 (IL-6) concentrations did not differ significantly between trials. LowCHO1.5% sport drink did not significantly differ from PLA in measured variables, which indicated that the amount and rate of carbohydrate ingestion (15 g, 10 g/h) in low-carbohydrate sport drink was not enough to significantly protect from the stress induced by high-intensity long-distance running, whereas the ingestion of CHO7% (45 g/h) blunted the significant cortisol response and significantly decreased the leukocyte response.